2018
DOI: 10.1182/bloodadvances.2018019547
|View full text |Cite
|
Sign up to set email alerts
|

A β1-tubulin–based megakaryocyte maturation reporter system identifies novel drugs that promote platelet production

Abstract: During maturation, megakaryocytes (MKs) express β1-tubulin (TUBB1) and rearrange their microtubule components to enlarge, form proplatelets, and eventually release platelets. The development of a platform to identify in vitro conditions that would efficiently promote MK development could potentially enable large-scale platelet production. Here, we show that an immortalized MK cell line (imMKCL) genetically modified to express the β1-tubulin-Venus reporter provides a practical system to efficiently monitor the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Previous studies demonstrated that SR1 promoted MK differentiation and maturation in addition to its effect on HSC expansion. 22,23 On the other hand, little is known about the effect of VPA and C433 on megakaryopoiesis. We then focused on the assessment of VPA and C433 on differentiating SMC-expanded CD34 + cells toward the megakaryocytic lineage.…”
Section: Effect Of Three Small Molecules On Mk Differentiation and Mamentioning
confidence: 99%
“…Previous studies demonstrated that SR1 promoted MK differentiation and maturation in addition to its effect on HSC expansion. 22,23 On the other hand, little is known about the effect of VPA and C433 on megakaryopoiesis. We then focused on the assessment of VPA and C433 on differentiating SMC-expanded CD34 + cells toward the megakaryocytic lineage.…”
Section: Effect Of Three Small Molecules On Mk Differentiation and Mamentioning
confidence: 99%
“…Lin − Sca1 + kit + Flt3 + HSCs are highly proliferative and show lymphoid or myeloid differentiation potential, but lack E-Mk potential. Treatment with Flt3 inhibitor also promotes significantly increased platelet-like particle production from MK cell line (5). To address the association of Flt3 and Mk development, we reviewed bone marrow biopsy from patient with and without Flt3 mutation and found that patients with Flt3 mutants showed statistically higher numbers of megakaryocytes in post-therapy marrows.…”
Section: Discussionmentioning
confidence: 99%
“…During hematopoiesis, megakaryocytes (Mk) develop from hematopoietic stem cells (HSCs) under tight control of Wnt/b-catenin signaling (3,4). Seo and colleagues demonstrated that Wnt signaling inhibitor, Wnt-C59, and Flt3 inhibitor, TCS 359, significantly increased platelet-like particle production from Mk supporting the crucial role of Wnt signaling pathway and Flt3 in Mk development and maturation (5).…”
Section: Introductionmentioning
confidence: 99%
“…Through an assessment of relevant substances or drugs, we found that the combination of a ROCK inhibitor and an AhR antagonist enables platelet generation without feeder cells for imMKCL cultivation [ 73 ]. For further high-throughput screening of drugs that enhance megakaryocyte maturation, we developed an imMKCL with a fluorescent reporter that correlates with the expression of a maturation-specific protein [ 106 ].…”
Section: Development Of Ipsc-pltsmentioning
confidence: 99%